The effectiveness of procurement contract towards achieving value for money in procurement of works - Andrew, Chengelela (Mzumbe University, 2024)
Dissertation Submitted in partial fulfillment of the Requirements for the Master Degree of Science in Procurement and Supply Chain Management 2018